2020
DOI: 10.1177/0886260520917517
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in Emotion Regulation and Cyberbullying Among Chinese Adolescents: A Mediation Model of Loneliness and Depression

Abstract: Recent research has ascertained some risk factors for cyberbullying. However, few studies have investigated the potential influence of difficulties in emotion regulation (DER) on cyberbullying, and there is little knowledge about the mediating mechanisms underlying this association. This study investigated whether DER would be significantly related to adolescent cyberbullying and whether loneliness and depression would sequentially mediate the link between DER and adolescent cyberbullying. A sample of 719 Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…Higher rate in LGBTQ+ community [36] Other online behaviours Associated with Internet addiction and using the Internet >2 hours/day [16,37] Higher in subjects with PUI [11,29] Association with online gaming disorder [28] Association with online gaming disorder [28] --Predicted by higher social media addiction scores and more hours spent online [27] Parent-child relationship Association with parental abuse, parental neglect, and family dysfunction [26] Predicted by childhood psychological maltreatment [38] Association with physical discipline by parents [28] Higher risk in adolescents with a high level of parental phubbing [39] Psychological factors Higher severity in subjects with social avoidance and social distress, in particular with peers [40] Associated with higher impulsivity or difficulties in emotions regulation [23,41,42] -Higher risk in adolescents with antisocial behaviours or conduct problems [23,43,44]…”
Section: Minority Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher rate in LGBTQ+ community [36] Other online behaviours Associated with Internet addiction and using the Internet >2 hours/day [16,37] Higher in subjects with PUI [11,29] Association with online gaming disorder [28] Association with online gaming disorder [28] --Predicted by higher social media addiction scores and more hours spent online [27] Parent-child relationship Association with parental abuse, parental neglect, and family dysfunction [26] Predicted by childhood psychological maltreatment [38] Association with physical discipline by parents [28] Higher risk in adolescents with a high level of parental phubbing [39] Psychological factors Higher severity in subjects with social avoidance and social distress, in particular with peers [40] Associated with higher impulsivity or difficulties in emotions regulation [23,41,42] -Higher risk in adolescents with antisocial behaviours or conduct problems [23,43,44]…”
Section: Minority Groupsmentioning
confidence: 99%
“…Immediate consequences for affected adolescents can include psychological distress, academic difficulties, loneliness, reduced wellbeing [41,49]. A recent meta-analysis [50] of 57 empirical studies from 17 countries showed a significant correlation between CBB victimization and depression.…”
Section: Burden Of Cyberbullying and Public Health Costmentioning
confidence: 99%
“…For example, with the fast development of Internet infrastructure in China, 99.2% of the children and adolescents were found to access the Internet frequently in 2020, and 78% of them had started to use the Internet service under the age of 10 ( Ji and Shen, 2020 ). Cyberbullying involvement can also lead to various mental health, social-psychological, and behavioral problems ( Kwan et al, 2020 ), and loneliness can be one of such results ( Segrin et al, 2012 ; Jiang et al, 2020 ). Considering the double impact of Covid-19 and cyberbullying on children and adolescents and the ongoing pandemic, there is a strong need to study the correlations between cyberbullying involvement and loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…Deters and Mehl (2013) explain that university students may use SM to help reduce their feelings of loneliness because they have to be separated from their families when attending university, and this, in turn, leads to an increased risk of becoming a victim of cyberbullying. In addition, previous studies have found that the feeling of loneliness is associated with and mediates the relationship between emotional regulation and adolescent cyberbullying (Larrañaga et al, 2016) (Cava et al, 2020) (Jiang et al, 2020). However, contrary to this, a study by (Yubero et al, 2017) analyzed the relationship between cyberbullying victimization and social and emotional factors (including perpetration, loneliness, self-esteem, and perceived acceptance by friends) in university students, and found that loneliness was not associated with being a victim of cyberbullying.…”
Section: Personal Factorsmentioning
confidence: 94%